The experience of diversity in open spaces of two historical towns in Malaysia - Harun, Nor Zalina; Mansor, Mazlina; Said, Ismail (Elsevier, 2013)
This paper explores diversity of open space as one of the salient parameters for good public place making in the built environment. Two open spaces in colonial towns of Taiping and Georgetown were selected as study sites. This paper is exploratory in nature, which applied descriptive and affective analysis on the users' experiences of the two open spaces. Diversity in both open spaces are characterized by the combination of richness in natural landscape elements, spaces, distribution of activity patterns, visual stimulants, strong historical, cultural and social significances. The study suggests that diversity means socialization, which can be achieved through gradual and natural occurring assimilation.